Can endurance athletes benefit from vegetarian diets? - Klementyna Dmowska; Justyna Kaczanowska; Emilia Zalewska (Nicolaus Copernicus University in Toruń, 2024)
The performance of an athlete is the result of a complex interplay of various factors, with diet representing a particularly crucial component. Nutritional profiles of vegetarian diets vary considerably from those of omnivorous diets. In our research, we propose that vegetarian diets may offer advantageous properties for endurance sportsmen. This review examines the distinctions between vegetarian and omnivorous diets and addresses these differences in the context of the nutritional requirements of athletes. The initial focus is on fundamental nutrients, including carbohydrates, proteins, and fats. Subsequently, the emphasis shifts to micronutrients. This analysis also encompasses the challenges and advantages associated with vegetarian diets. The subsequent section concerns the cardiovascular system, which is arguably the most crucial for endurance athletes. It examines the interaction between the cardiovascular system and other physiological factors, including dyslipidaemia, blood pressure and body weight. It also considers the impact of dietary modifications on these parameters and their influence on athletic performance. Finally, the recent research on the effects of a vegetarian diet on the performance of endurance athletes is presented. Despite a lack of conclusive evidence, recent research suggests that vegetarian diets may confer certain benefits, particularly in terms of endurance training. Although there is a paucity of rigorous research in this field, the existing evidence suggests that these dietary regimens may result in overall enhanced health and improved outcomes.